2020
DOI: 10.1155/2020/7987356
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction, Oral Health Practices, Clinical Outcomes, and Self-Perceived Oral Health in Young Saudi Adults

Abstract: The study assessed the relationship between Internet addiction and oral health practices and clinical outcomes and whether this was affected by oral health perception. In 2017, a cross-sectional study included university students in the Eastern Province of Saudi Arabia. Questionnaires assessed demographic background, oral health practices (consuming sugar, tobacco use, and oral hygiene), perceived oral health, and Internet addiction. Caries experience and gingivitis were assessed using the World Health Organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…Karacic et al ( 127 ) found a strong correlation between German adolescents' health-related quality of life, mental health, and problematic internet use; thus, suggesting that problematic internet use negatively influences health outcomes and requires further research attention ( 127 ). A recent study for Saudi young adults concluded that poor oral hygiene behaviors were significantly associated with problematic internet use ( 128 ). The negative impact of problematic internet use on oral health KAB was not significant among our participants, which might be attributed to the fact that dental students represent an above-average subset of the general youth population in terms of oral health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Karacic et al ( 127 ) found a strong correlation between German adolescents' health-related quality of life, mental health, and problematic internet use; thus, suggesting that problematic internet use negatively influences health outcomes and requires further research attention ( 127 ). A recent study for Saudi young adults concluded that poor oral hygiene behaviors were significantly associated with problematic internet use ( 128 ). The negative impact of problematic internet use on oral health KAB was not significant among our participants, which might be attributed to the fact that dental students represent an above-average subset of the general youth population in terms of oral health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the participants, 283 (62.7%), were males, in contrast to studies conducted by Freire et al [22] and Al-Ansari et al [23], where most of them were females, 312 (62%) and 712 (75.4%), respectively. More than half of the participants, 276 (61.2%), were unmarried, belonging to urban areas, 600 (66.5%), and unemployed, 193 (42.8%), which could be attributed to the fact that this sector of the population has greater spare time and ease of access to the Internet to be able to surf across social media platforms much more frequently.…”
Section: Demographic Characteristicsmentioning
confidence: 56%
“…The study participants acknowledged that social media contents encourage tobacco consumption in different ways (p≤0.001), which is consistent with research from Korea [ 31 ] and Taiwan [ 32 ] that found higher rates of tobacco users, lifetime smokers, or potential smokers among problematic Internet users. In addition, Al-Ansari et al [ 23 ] reported that in their study of young Saudi adults, participants who rated their dental health as good and who used the Internet sometimes or sporadically scored lower on tobacco use than those who used it problematically. Additionally, it aligns with a study conducted by Iranian university students, which found that smokers had a higher problematic Internet score than non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a negative association was revealed between problematic Internet use and frequent tooth-brushing and a direct association between problematic Internet use and poor oral health and oral symptoms [ 27 ]. Al-Ansari et al’s study showed that, among participants with good and fair perception of oral health, average and frequent Internet users had less negative oral health practices (sugar and tobacco consumption) and more positive oral health practices (oral hygiene) than participants with problematic Internet use [ 28 ].…”
Section: Discussionmentioning
confidence: 99%